Volcanic gas changes prior to Stromboli's major explosions are statistically significant - Alessandro Aiuppa; Marcello Bitetto; Luciano Curcio; Dario Delle Donne; João Lages; Giovanni Lo Bue Trisciuzzi; Giancarlo Tamburello; Angelo Vitale; Flavio Cannavò; Mauro Coltelli; Diego Coppola; Lorenzo Innocenti; et al. (Journal of Volcanology and Geothermal Research, 2025)

Source apportionment of major ions and trace elements in the atmospheric deposition of Palermo (Sicily, Italy) - Filippo Brugnone; Walter D'Alessandro; Marcello Liotta; Marcello Bitetto; Luciana Randazzo; Sergio Bellomo; Lorenzo Brusca; Giovanna Cilluffo; Francesco Parello; Sergio Calabrese (Atmospheric Pollution Research, 2025)

Improved volcanic SO2 flux records from integrated scanning-DOAS and UV Camera observations. - Giovanni Lo Bue Trisciuzzi; Alessandro Aiuppa; Giuseppe Salerno; Marcello Bitetto; Luciano Curcio; Lorenzo Innocenti; Giorgio Lacanna; Joao Pedro Nogueira Lages; Francesco Maria Lo Forte; Salvatore Roberto Maugeri; Filippo Murè; Paolo Principato; et al. (Journal of Volcanology and Geothermal Research, 2024)

CO2 emissions during the 2023 Litli Hrútur eruption in Reykjanes, Iceland: ẟ13C tracks magma degassing - Tobias P. Fischer; Céline L. Mandon; Scott Nowicki; John Ericksen; Felipe Rojas Vilches; Melissa A. Pfeffer; Alessandro Aiuppa; Marcello Bitetto; Angelo Vitale; G. Matthew Fricke; Melanie E. Moses; Andri Stefánsson (Bulletin of Volcanology, 2024)

Correction to: Volcanic activity and gas emissions along the South Sandwich Arc - Emma J. Liu; Kieran Wood; Alessandro Aiuppa; Gaetano Giudice; Marcello Bitetto; Tobias P. Fischer; Brendan T. McCormick Kilbride; Terry Plank; Tom Hart (Bulletin of Volcanology, 2021)

Volcanic activity and gas emissions along the South Sandwich Arc - Emma J. Liu; Kieran Wood; Alessandro Aiuppa; Gaetano Giudice; Marcello Bitetto; Tobias P. Fischer; Brendan T. McCormick Kilbride; Terry Plank; Tom Hart (Bulletin of Volcanology, 2021)
The South Sandwich Volcanic Arc is one of the most remote and enigmatic arcs on Earth. Sporadic observations from rare cloud-free satellite images—and even rarer in situ reports—provide glimpses into a dynamic arc system characterised by persistent gas emissions and frequent eruptive activity. Our understanding of the state of volcanic activity along this arc is incomplete compared to arcs globally. To fill this gap, we present here detailed geological and volcanological observations made during an expedition to the South Sandwich Islands in January 2020. We report the first in situ measurements of gas chemistry, emission rate and carbon isotope composition from along the arc. We show that Mt. Michael on Saunders Island is a persistent source of gas emissions, releasing 145 ± 59 t day −1 SO 2 in a plume characterised by a CO 2 /SO 2 molar ratio of 1.8 ± 0.2. Combining this CO 2 /SO 2 ratio with our independent SO 2 emission rate measured near simultaneously, we derive a CO 2 flux of 179 ± 76 t day −1 . Outgassing from low temperature (90–100 °C) fumaroles is pervasive at the active centres of Candlemas and Bellingshausen, with measured gas compositions indicative of interaction between magmatic fluids and hydrothermal systems. Carbon isotope measurements of dilute plume and fumarole gases from along the arc indicate a magmatic δ 13 C of − 4.5 ± 2.0‰. Interpreted most simply, this result suggests a carbon source dominated by mantle-derived carbon. However, based on a carbon mass balance from sediment core ODP 701, we show that mixing between depleted upper mantle and a subduction component composed of sediment and altered crust is also permissible. We conclude that, although remote, the South Sandwich Volcanic Arc is an ideal tectonic setting in which to explore geochemical processes in a young, developing arc.

The crater lake of Ilamatepec (Santa Ana) volcano, El Salvador: insights into lake gas composition and implications for monitoring - Nathalie Hasselle; Francisco Montalvo; Dmitri Rouwet; Angelo Battaglia; Marcello Bitetto; Demetrio Escobar; Eduardo Gutiérrez; Jacqueline Rivera; Ana Mirian Villalobos; Raffaello Cioni; J. Maarten de Moor; Tobias P. Fischer; et al. (Bulletin of Volcanology, 2019)

Dukono, the predominant source of volcanic degassing in Indonesia, sustained by a depleted Indian-MORB - Philipson Bani; Giancarlo Tamburello; Estelle F. Rose-Koga; Marco Liuzzo; Alessandro Aiuppa; Nicolas Cluzel; Iwan Amat; Devy Kamil Syahbana; Hendra Gunawan; Marcello Bitetto (Bulletin of Volcanology, 2018)